A comparative study on the anti-wrinkle benefits of an active complex (Palmitoyl Tripeptide-38, Silybum marianum fruit extract, Hyaluronic acid (HA), and Chenopodium quinoa seed extract) : Comparative Evaluation of the Anti-wrinkle Efficacy of Hyaluronic acid, Peptide, and Some Herbal extracts’ Complex - Hashemi, Nooshin; Eslahi, Ehsan; Shamaei, Sara (Aesthetic Medicine, 2023)
Background: recently, a wide range of natural polymers and plant extracts have been used to slow down aging and ameliorate the skin by reducing fine lines and wrinkles. Aims: This research investigates the efficacy of hyaluronic acid, palmitoyl tripeptide-38, and two rich herbal extracts in the form of a topical anti-wrinkle cream. Methods: the complex which was formulated using some active ingredients, was applied twice daily for 3 months in a group composed of 30 women, in the crow’s feet region. The improvement of the appearance of wrinkles in that area was assessed by a self-evaluation and the GAIS (Global aesthetic improvement) scale. In addition, the wrinkle depth and volume, skin moisture, and transepidermal water loss (TEWL) were measured using the Visioface, Tewameter, and Cutometer devices at baseline and after 6 and 12 weeks of treatment. Results: there were no noticeable adverse reactions including erythema, irritation, or allergic reactions after the treatment period. Clinical measurements showed an improvement in the subjective evaluation of the skin’s appearance by the GAIS scale in 14 and 17 of the participants in grade 1 of this scale after 6 and 12 weeks of treatment. The wrinkles’ volume and depth were significantly reduced (p<0.05). In addition, the skin’s moisture and gross and net elasticity increased after 12 weeks of treatment (p< 0.05). The skin transepidermal water loss also decreased to -22% after 12 weeks of application (p<0.05). Conclusions: the results of this study revealed that this topical cream, serves as a safe and reliable option for skin hydration and exerts powerful anti-aging benefits compared to the base formula.